New indexing of Revista de la Facultad de Medicina Humana: Harvard Library and DRJI: Nuevas indexaciones de la Revista de la Facultad de Medicina Humana: Harvard Library y DRJI - De la Cruz-Vargas, Jhony A. (2023)
The Revista de la Facultad de Medicina Humana de la Universidad Ricardo Palma (RFMH) reaches a momentous career achievement when indexed in the prestigious Harvard Library and the Directory of Research Journals Indexing (DRJI). This indexing reflects the journal's firm commitment to advancing medical science and public health through rigorous, high-quality publication.